Precambrian fault reactivation revealed by structural and K-Ar geochronological data from the spent nuclear fuel repository in Olkiluoto, southwestern Finland - Nordbäck Nicklas; Mattila Jussi; Zwingmann Horst; Viola Giulio (ELSEVIER, 2022)
Integrated structural/geochmnological studies help unraveling complex brittle deformation histories. We have analysed the structural geological database of brittle faults from the ONKALO (TM) underground facility for spent nuclear fuel in Olkiluoto in southwestern Finland. Based on the structural geological data from eleven representative fault zones, we classify the Olkiluoto brittle structural features into four fault systems, referred to as Fault system I to IV. The classification is based on their structural properties and tectonic history, crosscutting relationships, fault rock mineralogical characterization and 3D modelling. Some constraints on the timing of faulting are provided by K-Ar dates on synkinematic illite from fault gouge samples. Our results show that the bedrock in southwestern Finland experienced numerous brittle deformation phases between ca. 1.75 and 0.9 Ga. N-S strike-slip faults (Fault systems I and II) formed at mid-crustal levels ca. 1.79-1.75 Ga ago in response to NW-SE/NNW-SSE compression soon after the Svecofennian omgeny. Later E-W striking oblique dextral/normal faults (Fault system III) are tentatively associated with the Gothian omgeny 1.6 Ga ago. These three fault systems were reactivated during NE-SW compression ca. 1.3-1.2 Ga ago, coeval with intrusion of a regional swarm of olivine diabase sills. E-W compression at the onset of the Sveconorwegian omgeny ca. 1.1-1.0 Ga ago resulted in the formation of SE dipping low-angle thrust faults (Fault system IV) and the selective reactivation of fault system II and III. Overall E-W extension during the collapse of the Sveconorwegian orogen ca. 0.97-0.87 Ga ago caused the localised reactivation of fault systems III and IV. Our research approach, which is integral to the siting process of repositories for spent nuclear fuel, demonstrates that the basement in southwestern Finland experienced repeated reactivation since the Mesoproterozoic, suggesting that future deformation localization is likely to be also accommodated by reactivation of existing brittle structures rather than formation of new faults.